Guff : um sistema para desenvolvimento de jogos - Valente, Luis Paulo Santos (2008)
Computer games apply concepts from several fields of Computer Science such as Computer Graphics, Software Engineering, Artificial Intelligence and Computer Networks, among others. Additionally, computer games may be regarded as interactive real-time applications, where performance is one of the key considered aspects. However, this concern about efficient algorithm execution (as well as visual presentation) has led to the recurring practice of implementing all the required functionality to develop a game in a new project. As game development complexity increases, this practice is becoming infeasible. Hence, it's necessary to seek other approaches for game development. This work, besides initiating a new reasearch field at UFF related to game develoment, presents the design and implementation of the Guff (games-uff) framework, which will be improved in further works in this research field. A game framework offers a reusable architecture for development of new games.